A Self-Applied Multi-Component Psychological Online Intervention Based on UX, for the Prevention of Complicated Grief Disorder in the Mexican Population During the COVID-19 Outbreak: Protocol of a Randomized Clinical Trial - Dominguez-Rodriguez, Alejandro; Martínez-Luna, Sofia Cristina; Hernández Jiménez, María Jesús; De La Rosa-Gómez, Anabel; Arenas-Landgrave, Paulina; Esquivel Santoveña, Esteban Eugenio; Arzola-Sánchez, Carlos; Alvarez Silva, Joabián; Solis Nicolas, Arantza Mariel; Colmenero Guadián, Ana Marisa; Ramírez-Martínez, Flor Rocio; Vargas, Rosa Olimpia Castellanos (Frontiers in Psychology, 2021)
Background: COVID-19 has taken many lives worldwide and due to this, millions of persons are in grief. When the grief process lasts longer than 6 months, the person is in risk of developing Complicated Grief Disorder (CGD). The CGD is related to serious health consequences. To reduce the probability of developing CGD a preventive intervention could be applied. In developing countries like Mexico, the psychological services are scarce. Self-applied interventions could provide support to solve this problem and reduce the health impact even after the pandemic has already finished. Aims: To design and implement a self-applied intervention composed of 12 modules focused on the decrease of the risk of developing CGD, and increasing the life quality, and as a secondary objective to reduce the symptomatology of anxiety, depression, and increase of sleep quality. The Intervention Duelo COVID (Grief COVID), follows the principles of User Experience (UX) and is designed according to the needs and desires of a sample of the objective participants, to increase the adherence to the self-applied intervention, considered one of the main weaknesses of online interventions. Methods: A Randomized Controlled Trial will be conducted from the 22nd of December of 2020 to the first of June 2021. The participants will be assigned to an intervention with elements of Cognitive Behavioral Therapy, Acceptance and Commitment Therapy, Mindfulness and Positive Psychology. The control group will be a wait-list condition, that will receive the intervention 1.5 to 2 months after the pre-measurement were taken. The Power Size Calculation conducted through G*Power indicated the need for a total of 42 participants, which will be divided by 21 participants in each group. The platform will be delivered through responsive design assuring with this that the intervention will adapt to the screen size of cellphones, tablets, and computers. Ethics and dissemination: The study counts with the approval of the Research Ethics Committee of the Autonomous University of Ciudad Juárez, México, and it is registered in Clinical Trials (NCT04638842). The article is sent and registered in clinical trials before the recruitment started. The results will be reported in future conferences, scientific publications, and media.